Global trends and spatial drivers of diabetes mellitus mortality, 1990-2019: a systematic geographical analysis - Xu, Zejia; Feng, Jianheng; Xing, Siyi; Liu, Yin; Chen, Yuting; Li, Jie; Feng, Yunhui (Frontiers in Endocrinology, 2024)
Objective: Diabetes mellitus is the leading cause of death worldwide, and multiple risk factors affect associated with diabetes mortality.Employing spatial statistics, we characterized the spatial distribution and patterns of diabetes mortality, and revealed the spatial relationship between diabetes mortality and 11 socioeconomic and environmental risk factors at the country level, from 1990 to 2019.Globally, significantly high rates of diabetes mortality were primarily clustered in countries with limited land areas or located on islands, such as Fiji, Kiribati, Eswatini, and Trinidad and Tobago.countries within Oceania, the Caribbean, and Southern Africa. Countries with weaker economic independence are more likely to have higher diabetes mortality rates. In addition, the impact of socioeconomic and environmental factors was significant at the country level, involving health expenditure, number of physicians, household and ambient air pollution, smoking, and alcohol consumption. Notably, the spatial relationship between diabetes mortality and ambient air pollution, as well as alcohol consumption, showed negative correlations. Countries with high diabetes mortality rates generally had lower levels of ambient air pollution and alcohol consumption.The study highlights the spatial clustering of diabetes mortality and its substantial variation. While many risk factors can influence diabetes mortality, it's 2 also essential to consider the level of these factors at the country level. Tailoring appropriate interventions based on specific national circumstances holds the potential to more effectively mitigate the burden of diabetes mortality.